Star wars: bounty hunters (2020), volume 2 ebook - Sacks, Ethan (Star Wars: Bounty Hunters (2020), 2021)
Collects Star Wars: Bounty Hunters (2020) #6-11. With precious cargo and a price on his head, Valance must turn to the one person he can trust. But the Unbroken Clan has sent a unique and deadly pair of bounty hunters after him: No one in the galaxy can escape the combined cunning of 4-LOM and Zuckuss! Wounded and on the run, Valance reunites with a long-lost love in a secret rebel base — but the deadliest bounty-hunting duo in the galaxy is closing in, and they brought an army of Clone War–era battle droids with them! As Valance makes a desperate gambit to survive, he'll risk the wrath of pirates in the Outer Rim…and set himself on a collision course with his old rival Dengar! Plus: Bossk finds himself the hunted rather than the hunter on the forest world of Malastare!